1999
DOI: 10.1074/jbc.274.43.30906
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Heparin Binding Domain of Fibronectin in Cooperation with the V Region Induce Decreases in pp125 Levels Plus Proteoglycan-mediated Apoptosis via Caspases

Abstract: Intact fibronectin (FN) protects cells from apoptosis.When FN is fragmented, specific domains induce proteinase expression in fibroblasts. However, it is not known whether specific domains of FN can also regulate apoptosis. We exposed fibroblasts to four recombinant FN fragments and then assayed for apoptosis using criteria of cellular shape change, condensed nuclear morphology, and DNA fragmentation. The fragments extended from the RGD-containing repeat III10 to III15; they included (V FAK levels and regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 41 publications
1
65
0
Order By: Relevance
“…As previously shown, [1][2][3] an altered FN matrix consisting of the V þ HÀ protein induced apoptosis in primary ligament fibroblasts (Figure 1a and b). Cells treated with an altered FN matrix exhibited nuclear condensation and bright DAPI staining typical of apoptotic cells.…”
Section: Resultsmentioning
confidence: 55%
“…As previously shown, [1][2][3] an altered FN matrix consisting of the V þ HÀ protein induced apoptosis in primary ligament fibroblasts (Figure 1a and b). Cells treated with an altered FN matrix exhibited nuclear condensation and bright DAPI staining typical of apoptotic cells.…”
Section: Resultsmentioning
confidence: 55%
“…Fn is a multifunctional protein whose activities are due to functional domains present both in the native ''full-length'' protein 16,17 and its multiple sub-fragments. Indeed, when released by limited proteolysis, these functional domains display specific activities, latent in the native Fn.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on fibronectin and its integrin-mediated signaling pathways. Fibronectin is critical for transducing survival signals in various cell types (29,35), and blocking fibronectin/integrin-mediated signals by various methods leads to apoptosis or anoikis (38). Thus, the reduced apoptosis of multicellular aggregates in suspension cultures suggested that resistance to anoikis involves survival signals from fibronectin.…”
Section: Discussionmentioning
confidence: 99%